Characteristics of the gut microbiota and the effect of Bifidobacterium in very early-onset inflammatory bowel disease patients with IL10RA mutations - Xu, Xu; Gao, Yuanqi; Xiao, Yuan; Yu, Yi; Huang, Jiebin; Su, Wen; Li, Na; Xu, Chundi; Gao, Shenshen; Wang, Xinqiong (Frontiers in Microbiology, 2024)
Very early-onset inflammatory bowel disease (VEO-IBD) is a distinct subtype of inflammatory bowel disease (IBD) characterized by onset before the age of 6 years, and patients often exhibit more severe clinical features. Interleukin 10 receptor alpha (IL10RA) is a hotspot mutation in the Chinese population and is associated with a poor prognosis closely linked to the onset of IBD. However, limited knowledge exists regarding how the IL10RA mutation influences the host microbiota and its role in disease development. We employed 16S rRNA sequencing to conduct a comprehensive assessment of microbial changes in different types of IBD, employed database to thoroughly examine the influence of Bifidobacterium in IBD and to demonstrate a potential positive effect exerted by Bifidobacterium breve M16V (M16V) through a mouse model. The study demonstrated a significant reduction in the abundance and diversity of the gut microbiota among children with IL10RA mutations compared to those with late-onset pediatric IBD and nonmutated VEO-IBD. Furthermore, the analysis identified genera capable of distinguishing between various types of IBD, with the genus Bifidobacterium emerging as a potential standalone diagnostic indicator and Bifidobacterium may also be involved in related pathways that influence the progression of IBD, such as the biosynthesis of amino acids and inflammation-related pathways. This study corroborated the efficacy of Bifidobacterium in alleviating intestinal inflammation. The impact of IL10RA mutations on VEO-IBD may be mediated by alterations in microbes. M16V demonstrates efficacy in alleviating colitis and holds promise as a novel microbial therapy.